Intraindividual comparison of [11C]acetate and [11C]choline PET for detection of metastases of prostate cancer - Kotzerke, J.; Volkmer, B. G.; Glatting, G.; van den Hoff, J.; Gschwend, J. E.; Messer, P.; Reske, S. N.; Neumaier, B. (Nuklearmedizin - NuclearMedicine, 2003)
In a pilot trial we investigated whether significant differences in prostate cancer (PCA) imaging would be observed using [11C]acetate and [11C]choline positron emission tomography (PET). Methods: Twelve patients were studied with both radiotracers. Whole body PET without attenuation correction was performed after injection of 0.95 ± 0.15 GBq [11C]acetate and 0.84 ± 0.13 GBq [11C]choline, respectively, from 5 to 60 min p. i. Focally increased uptake in bone, below the urinary bladder or in a lymph node region was considered as tumour. Primary tumour, lymph node involvement, bone metastases, local recurrence; and no evidence of disease were known in 2, 4, 2, 2; and 2 patients, respectively. Results: [11C]Acetate uptake was highest in spleen and pancreas while [11C]choline uptake was predominant in liver and kidney parenchyma. However, interindividual variation was high. The potential of both radiotracers to detect known bone lesions, lymph node metastases, and imaging of the primary tumour was identical. However, both failed to detect a small local recurrence in two patients as well as to demonstrate lymph node involvement in one patient, which was confirmed by surgery. Conclusions: In this preliminary study, uptake of both radiotracers in prostate cancer or its metastases was nearly identical and none of them should be favoured. At present, both radiotracers influence patient management by detection of local recurrence, lymph node, or bone metastases of PCA.
Keywords: Acetate; choline; positron emission tomography; prostate cancer